ОСОБЕННОСТИ КЛИНИЧЕСКОЙ КАРТИНЫ ДИФФУЗНОГО ТОКСИЧЕСКОГО ЗОБА У ДЕТЕЙ ВОРОНЕЖСКОЙ ОБЛАСТИ - Чернышова, Виктория Сергеевна; Стольникова, Тамара Георгиевна; Евтухова, Оксана Вячеславовна; Кулакова, Елена Николаевна (Медицина: теория и практика, 2020)